ASSESSING THE IMPACT OF NURSES’ ROLE ON PATIENT SATISFACTION IN MULTIDISCIPLINARY TEAM CARE (Journal of Medical & Health Sciences Review, 2025)
Introduction: The importance of Multidisciplinary Teams (MDTs) in modern healthcare delivery is growing rapidly.  In terms of MDTs, nurses participate actively in administering, managing and communicating the various levels of supportive care to patients fulfilling their needs. As nurses touch the patient, their contributions to MDTs are essential. Patient satisfaction is one of the key indicators of the healthcare system. Hence, these contributions need to be evaluated. Methodology: A cross-sectional study was conducted to focus on healthcare providers in Karachi, Pakistan. A sample size of 219 was calculated through OpenEpi Software. A convenience sampling technique was used to collect the data by adopting a structured questionnaire. Data analysis was conducted by utilizing SPSS version 26, incorporating descriptive statistics. Ethical approval was taken and informed consent was attained from the participants before data collection.Results: Out of 219 respondents, majority were females. Most of the study participants agreed that nurses coordinate care, facilitate information flow, and provide advocacy. Overall, 75.8% reported greater satisfaction with nursing care. However, staffing shortage and burnout were cited as challenges.Conclusion: Within the MDTs framework, nurses are central to patient satisfaction, and are the primary caregivers providing emotional support, communication, and coordination. However, nurse’s shortages and high workloads inhibit their productivity. Improved organizational support and equipping nurses with teamwork and leadership training are necessary to improve quality and patient-centered care.